Copepod carcasses as microbial hot spots for pelagic denitrification - Glud, Ronnie N.; Grossart, Hans-Peter (Prof. Dr.); Larsen, Morten; Tang, Kam W.; Arendt, Kristine E.; Rysgaard, Soren; Thamdrup, Bo; Gissel Nielsen, Torkel (Limnology and Oceanography, 2015)
Copepods are exposed to a high non-predatory mortality and their decomposing carcasses act as microniches with intensified microbial activity. Sinking carcasses could thereby represent anoxic microenvironment sustaining anaerobic microbial pathways in otherwise oxic water columns. Using non-invasive O-2 imaging, we document that carcasses of Calanus finmarchicus had an anoxic interior even at fully air-saturated ambient O-2 level. The extent of anoxia gradually expanded with decreasing ambient O-2 levels. Concurrent microbial sampling showed the expression of nitrite reductase genes (nirS) in all investigated carcass samples and thereby documented the potential for microbial denitrification in carcasses. The nirS gene was occasionally expressed in live copepods, but not as consistently as in carcasses. Incubations of sinking carcasses in (15)NO3-amended seawater demonstrated denitrification, of which on average 34%+/- 17% (n=28) was sustained by nitrification. However, the activity was highly variable and was strongly dependent on the ambient O-2 levels. While denitrification was present even at air-saturation (302 mol L-1), the average carcass specific activity increased several orders of magnitude to approximate to 1 nmol d(-1) at 20% air-saturation (55 mol O-2 L-1) at an ambient temperature of 7 degrees C. Sinking carcasses of C. finmarchicus therefore represent hotspots of pelagic denitrification, but the quantitative importance as a sink for bioavailable nitrogen is strongly dependent on the ambient O-2 level. The importance of carcass associated denitrification could be highly significant in O-2 depleted environments such as Oxygen Minimum Zones (OMZ).